Modeling the Transport and Utilization of Carbon and Nitrogen in a Nodulated Legume - Pate, John S. (1979)
An empirical modeling technique was developed for depicting quantitatively the transport and partitioning of photosynthetically fixed C and symbiotically fixed N during 10-day intervals of a 40-day period in the growth of nodulated plants of white lupin (Lupinus albus L. cv. Ultra). Model construction utilized data for C and N consumption of plant parts and C:N weight ratios of the xylem and phloem fluids serving specific plant organs. Formulas were derived from calculating the net transport of C and N between plant parts in xylem and phloem. The models provided quantitative information on the dependence of growing organs on xylem and phloem for their supply of C and N, the cycling of N through leaflets and of C through nodules, the extent of direct incorporation of fixed N into growing nodules, and the involvement of N from shoot translocate in the nutrition of the nodulated root. Stem plus petioles abstracted considerably more N from xylem than expected from their transpirational activity. Xylem to phloem transfer of recently fixed N in mature stem and petioles was substantiated by the models, being depicted as a device for dispensing N to growing parts of the shoot extra to that attracted transpirationally in xylem or received as translocate from leaflets.